Surgical management of stress urinary incontinence: A rational approach to treatment selection - Winters, J. Christian (Canadian Urological Association Journal, 2012)
There are a number of operative approaches to correct stress urinary incontinence (SUI). There is clearly not one procedure that “fits all.” This review provides a summary of key available data comparing the various interventions. These findings are then incorporated into an algorithm, which attempts to outline a rational approach to select the most appropriate procedures in women seeking surgical treatment of SUI.